Literacy Transformation Strategy through Reading Corner Optimization: Pedagogical Analysis and Practical Implementation Grade VIII Students at MTs Miftahul Mubtadiin Banyuwangi - Barata, Mahendra Aswit Sandra; Kurniawan, Nurhafit (Jurnal Bahasa Indonesia Prima (BIP), 2026)
The post-pandemic literacy paradox in Indonesia, characterized by an increase in PISA 2022 rankings amidst a decline in absolute scores, necessitates a reorientation of educational strategies from macro-policy scales toward micro-pedagogical interventions within the classroom. This research presents an in-depth investigation regarding literacy transformation through the optimization of "Reading Corners" at MTs Miftahul Mubtadiin, Muncar District, Banyuwangi Regency, a madrasah within the Minhajut Thullab Islamic Boarding School environment facing challenges in reading material accessibility. Surpassing conventional approaches that solely emphasize physical aspects, this study integrates the theoretical framework of Lev Vygotsky’s Social Constructivism and the philosophy of The Third Teacher from Reggio Emilia to reconstruct the classroom literacy ecosystem. Utilizing a mixed-methods explanatory sequential research design, this study involved 22 Grade VIII students as subjects of intensive intervention over eight weeks. Data simulation demonstrated a statistically significant improvement: average literacy competence increased from 54.32 to 78.91 (p<0.001), and the reading interest index surged from 45.23 to 82.14. Qualitative findings confirmed that the transformation of physical space combined with social scaffolding and the curation of culturally relevant books was capable of converting students' passive behavior into active participation. This research recommends a decentralized library model based in the classroom that is responsive to the needs of madrasah adolescents.